Perencanaan Pengembangan Gampong Mandiri Pangan Berbasis Partisipasi Masyarakat di Gampong Lam Manyang, Kecamatan Peukan Bada, Kabupaten Aceh Besar - Irin Caisarina; Mirza Irwansyah; Kustadi Suhendang; Najwa Najwa Alya Putri; Asmaul Husna; Annisa Zahra Imani; Eva Latifa; Ruhul Abshar; Atika Aditya (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2026)
Community-based rural development plays an important role in strengthening food security and improving community welfare. This community service activity aimed to formulate a participatory development plan for a food self-sufficient village in Gampong Lam Manyang, Peukan Bada District, Aceh Besar Regency. The village possesses significant natural resource potential, particularly in agriculture and fisheries, which can support the development of local food systems. However, several challenges remain, including limited infrastructure, low economic diversification, and suboptimal management of local resources. The implementation method applied a participatory approach involving field observation, community surveys, interviews, and group discussions with village officials and residents. These activities were conducted to identify village potentials, existing problems, and possible development strategies. Community participation was emphasized throughout the planning process to ensure that the proposed development plan aligns with local needs and conditions. The results indicate that Gampong Lam Manyang has strong potential to develop into a food self-sufficient village through the optimization of agricultural land, strengthening farmer institutions, improving village-owned enterprises (BUMG), and increasing community involvement in local economic activities. The proposed development plan includes strategies for improving agricultural productivity, strengthening local economic institutions, and encouraging sustainable use of village resources. The participatory planning process carried out in this community service activity demonstrates that community involvement can significantly contribute to sustainable village development and enhance local capacity in managing available resources effectively.